PERSONAL AND PROFESSIONAL VALUES IN PRIMARY CARE PHYSICIANS AND YOUR RELATION WITH BURNOUT SYNDROME - Segura Bernal, Jordi; Ferrer Ventura, Marta; Palma Sevillano, Carolina; Ger Cabero, Sandra; Domènech Cortés, Marga; Gutiérrez Blanch, Isabel; Cebriá Andreu, Jordi (Anales de Psicología / Annals of Psychology, 2006)
The aim of the current study was to analyse the differences in values of Primary Care doctors with high or low scores in burnout. 61 Primary Care doctors with extremely scores in burnout who participated in a longitudinal study started in 1999 were chose. In the first assessment were interviewed 528 subjects from Barcelona’s northern countries. There were used a sociodemographic questionnaire data, the Spanish version of the Maslach Burnout Inventory (MBI) and a values questionnaire that was validated in ICS (Institut Català de la Salut) workers sample. Statistically meaningful differences were observed in the following values between groups: Altruism (p=0,01), Confidentiality (p=0,013) y Abnega-tion (p=0,036). Data shows a direct correlation between Impatience-Emotional Exhaustion (p<0,05), inverse relations between Altruism-Emotional Exhaustion (p<0,01) and Altruism-Depersonalisation (p<0,05). The study shows some personal and professional values are associated with high or low levels of burnout. In the same way the conflict perception between personal and professional values could be associated with high scores in burnout.